Positive Creativity and the Intentions, Discretion, Problem Finding, and Divergent Thinking That Support It Can Be Encouraged in the Classroom - Mark A. Runco (MDPI AG, 2022)
This article begins by presenting a definition of positive creativity. This definition is based in part on the standard view of creativity, which points to originality and effectiveness. A brief discussion of the distinction between benevolent creativity and malevolent creativity indicates that intentions should also be required of positive creativity. Intentions may seem like difficult things to monitor in the classroom, but several useful methods are described herein. The suggestions that are offered here to support positive creativity involve divergent thinking and decision making. The most novel claim in this article is that positive creativity may involve not just problem solving but also problem finding. A second important claim is that educators must be prepared to take the good with the bad. More specifically, when creativity is encouraged, students are likely to think in truly divergent directions, which means they may offer negative as well as positive ideas. Educators should be prepared for ideas that they themselves do not understand. Practical suggestions are offered, including the recommendation that educators should encourage careful decision-making about what constitutes a worthwhile problem (as well as how to solve such problems in a creative fashion). Quite a few instances of malevolence take the form of pseudo-problems. These must be recognized as such and attention must be directed instead to the significant problems that do plague society, such as the climate crisis, the protection of voting rights, and racial discrimination. Positive creativity is needed now more than ever before.